SMART Method to Choose The Best Smartphone - Purnama, Pradani Ayu Widya; Armonitha, Shary; Rahmi, Nadya Alinda; Pohan, Nurmaliana (AI Society & STMIK Indonesia, 2024)
Smartphones are important devices for many people and are considered a necessity in today's industrial age 4.0. This is the beginning of the advancement of digital technology and the internet, where information can be easily accessed in various places. Therefore, people started buying smartphones. With this, people can utilise the Decision Support System. used to determine the data criteria needed to select a smartphone. With these criteria, users can accurately and quickly determine their choice. Where in the research in choosing a smartphone according to the needs of the community using 9 criteria that are often taken into consideration including Brand, Price, Processor Specifications, RAM Specifications, Model, Battery Capacity, Camera Resolution, Internal Capacity, Screen size which will be processed using the SMART method. Where the weight for each criterion has a value range of 0-100 depending on the priority given to each criterion. Based on calculations using the SMART method, the Iphone 11 Pro smartphone ranks highest with a final score of 8.3.